N170 Reveals the Categorical Perception Effect of Emotional Valence - Qiu, Ruyi; Wang, Hailing; Fu, Shimin (Frontiers in Psychology, 2017)
As an important attribute of facial expression, emotional valence has been well explored, but its processing mechanisms remain ambiguous. Investigating the categorical perception (CP) of emotional valence might help uncover the objective basis of the subjective dichotomy of emotional valence and identify the stage at which this processing of valence information might occur. A judgment task was used in the current study with stimuli from the within- or between-category condition, in which participants were required to decide whether two presented faces showed the same emotion. The results of the behavioral experiment revealed a significant CP effect of emotional valence, with faster RTs and greater accuracy for the between- than for the within-category stimuli. In the ERP experiment, the N170 (peaking at approximately 150-170 ms) was found to reflect the CP effect of emotional valence, with a larger amplitude for the within- than for the between-category condition. In contrast, the P1 component (peaking at approximately 100-130 ms) was insensitive to the CP effect of emotional valence. These results reveal the existence of the CP of emotional valence and indicate that the N170 is its earliest electrophysiological index. Therefore, the categorization of emotional valence not only has an objective neural basis but occurs at a relatively early stage of processing.